2018
DOI: 10.1016/j.bbi.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal prenatal depression predicts infant negative affect via maternal inflammatory cytokine levels

Abstract: Maternal depressive symptoms during pregnancy are associated with risk for offspring emotional and behavioral problems, but the mechanisms by which this association occurs are not known. Infant elevated negative affect (increased crying, irritability, fearfulness, etc.) is a key risk factor for future psychopathology, so understanding its determinants has prevention and early intervention potential. An understudied yet promising hypothesis is that maternal mood affects infant mood via maternal prenatal inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(57 citation statements)
references
References 121 publications
3
52
1
1
Order By: Relevance
“…All ASD (n = 54,071) stratified by ASD with intellectual disability, as elevated midgestational levels of numerous cytokines and chemokines such as GM-CSF, IFN-c, IL-1a and IL-6 are associated with ASD with intellectual disability, when compared to mothers of children with either ASD without intellectual disability, developmental delay or general population controls (Jones et al, 2017). In terms of mediation, while very little data exist in humans, a recent study has shown that maternal depressive symptoms are associated with higher maternal inflammation, including IL-6, and this mediated the effect on maternal report of infant negative affect (Gustafsson et al, 2018), a known risk factor for later adverse neurological outcomes. This may also suggest that preeclampsia-induced elevations in maternal IL-6 may act as a mediator of the preeclampsia-ASD association.…”
Section: Discussionmentioning
confidence: 99%
“…All ASD (n = 54,071) stratified by ASD with intellectual disability, as elevated midgestational levels of numerous cytokines and chemokines such as GM-CSF, IFN-c, IL-1a and IL-6 are associated with ASD with intellectual disability, when compared to mothers of children with either ASD without intellectual disability, developmental delay or general population controls (Jones et al, 2017). In terms of mediation, while very little data exist in humans, a recent study has shown that maternal depressive symptoms are associated with higher maternal inflammation, including IL-6, and this mediated the effect on maternal report of infant negative affect (Gustafsson et al, 2018), a known risk factor for later adverse neurological outcomes. This may also suggest that preeclampsia-induced elevations in maternal IL-6 may act as a mediator of the preeclampsia-ASD association.…”
Section: Discussionmentioning
confidence: 99%
“…Online Supplementary Table ST2 provides further details of the NOS assessment and criteria for cross-sectional (Herzog et al, 2013;Anthony and Lin, 2018) and online Supplementary Table ST3 for cohort studies (Wells et al, 2014a(Wells et al, , 2014b. The NOS assessment of the reviewed studies highlights the limited quality of available evidence: of the 10 reviewed studies 40% were defined as 'poor' (Scrandis et al, 2008;Azar and Mercer, 2013;Cheng and Pickler, 2014;Gustafsson et al, 2018), 50% as 'fair' (Christian et al, 2009;Cassidy-Bushrow et al, 2012;Haeri et al, 2013;Simpson et al, 2016;Osborne et al, 2018), and 10% as 'good' (Blackmore et al, 2011) based on the NOS assessment. Online Supplementary Table ST1 also shows that the findings are mixed with some studies showing that maternal depression is associated with higher levels of a number of inflammatory markers studied and some reporting null associations.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic factors, such as inherited genetic risk, and epigenetic modifiers influence stress neurobiology in model systems and in humans. Immune activation differences resulting from prior exposures can regulate the neural and behavioral impact of subsequent stressors (Kerr et al, 2005;Clark et during pregnancy could not only alter maternal hypothalamic pituitary adrenal axis (HPA) axis and immune function, but also shape neurodevelopmental trajectories and stress responsiveness in offspring (Ja sarevi c et al, 2017;Carlson et al, 2018;Davidson et al, 2018;Gustafsson et al, 2018;Rasmussen et al, 2019;Spann et al, 2018;Thompson et al, 2018;Graham et al, 2019).…”
Section: Embracing Complexitymentioning
confidence: 99%